'Naturally Fearful': Emotion, Race and French–Papuan Encounters, 1818–30. Issue 4 (1st October 2016) - Starbuck, Nicole
ABSTRACT: This paper traces perceptions of Papuan 'fearfulness' in the records of the Freycinet, Duperrey and Dumont d'Urville expeditions. These French scientific expeditions explored Oceania during the period of the Bourbon Restoration in France and stopped at Waigeo Island and Teluk Doreri in West Papua. The paper aims to elucidate not only the nature and significance of perceptions of fearfulness in the Papuan encounters, but also the Indigenous agency, French cultural assumptions and evolving ethnographic practices that complicated and were papered over by emergent 'racial' classifications. Despite their acknowledgement of diversity and their increasing familiarity with their hosts, the voyagers presented fearfulness as the Papuans' most characteristic trait. A hardening of this claim in the published accounts may be attributed partly to the development of a racial classification and distancing from the emotional intensity and complexity of contact, but that in itself leaves unclear what role fearfulness actually played in the encounters.